The Relationship between High Fiber Diet and Severity of Premenstrual Syndrome Symptoms in Medical Students of Pelita Harapan University - Ignatius Kelvin; Dwi Savitri Rivami (Fakultas Kedokteran Universitas Pelita Harapan, 2022)
Introduction: 47.8% of women worldwide experience symptoms of premenstrual syndrome and 20% of women experience symptoms that are severe enough to interfere with daily activities. This occurs during the last 14 days of the menstrual cycle or luteal phase, and it is caused by hormonal fluctuations.Aim: This study is going to be conducted to determine the relationship between a high fiber diet and the severity of premenstrual syndrome in adolescents.Method: This study used a comparative analytic categorical study with two unpaired categories with a cross-sectional study design. The research sample is female students at the Faculty of Medicine, the University of Pelita Harapan who met the inclusion criteria of at least 74 samples by judgmental sampling. Data were collected using a questionnaire in the form of a Premenstrual Symptom Scale, Estimated Food Record and Perceived Stress Scale with the chi-square method, and data analysis using SPSS 24.0. Results: There were 85 samples that matched the inclusion and exclusion criteria of this study. The majority of the sample came from the 2018 class (64.7%), 20 years old (61.2%), experiencing moderate stress (61.2%), and having a normal body mass index (72.9%). The researcher found a p-value of 0.309 (p> 0.05), which means that there is no significant relationship between a high-fiber diet and the severity of premenstrual syndrome symptoms.